Spatial differentiation for sample selection models - Alexander Klein; Guy Tchuente Nguembu (University of Kent, School of Economics, 2017)
This paper uses spatial differencing to estimate parameters in sample selection models with unobserved heterogeneity. We show that under the assumption of smooth changes across the space of unobserved site-specific heterogeneity and selection probability, key parameters of a sample selection model are identified. A simple estimation procedure is proposed and the formula for the estimator of the standard error is derived.
Keywords: C13; C31; 330; Sample selection; spatial difference; instrumental variable